Integration of Islamic Values in Learning Evaluation to Improve the Quality of Islamic Education - Achmad Farihin; Bahrani Bahrani (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
Learning evaluation is a central component in determining educational quality; however, evaluation practices in Islamic education often remain dominated by cognitive and summative orientations, limiting their ability to support holistic educational goals. This study explores the integration of Islamic values into learning evaluation as a strategy for improving the quality of Islamic education. Using a qualitative literature review, this research analyzes and synthesizes findings from 20 selected national and international journal articles on learning evaluation, Islamic education, and value-based assessment. Data were examined through descriptive tabulation and thematic analysis to identify dominant patterns and conceptual relationships. The findings reveal that learning evaluation in Islamic education is gradually shifting toward more holistic practices that integrate cognitive, affective, and spiritual dimensions. The integration of Islamic values, such as honesty, responsibility, discipline, and moral integrity, enables evaluation to function not only as a technical measurement tool but also as a pedagogical and moral process that supports character formation. Evidence from program evaluation, instructional assessment instruments, and subject-based learning indicates that value-based evaluation can be applied across educational levels and disciplines. This study concludes that integrating Islamic values into learning evaluation is a foundational approach to strengthening the quality of Islamic education by aligning academic achievement with ethical and spiritual development.